2016
DOI: 10.1016/j.redox.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Macroautophagy is impaired in old murine brain tissue as well as in senescent human fibroblasts

Abstract: The overall decrease in proteolytic activity in aging can promote and accelerate protein accumulation and metabolic disturbances. To specifically analyze changes in macroautophagy (MA) we quantified different autophagy-related proteins (ATGs) in young, adult and old murine tissue as well as in young and senescent human fibroblasts. Thus, we revealed significantly reduced levels of ATG5-ATG12, LC3-II/LC3-I ratio, Beclin-1 and p62 in old brain tissue and senescent human fibroblasts. To investigate the role of mT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 45 publications
(57 reference statements)
1
58
0
Order By: Relevance
“…As EP2 signaling contributes to senescence in fibroblasts [72], and EP2 deletion reduces oxidative damage and severity of Alzheimer's disease [73], which suggests EP2 signaling as a potential link between defective autophagy and senescence/aging. Recently, it was shown, that in aged dermal fibroblasts and brain tissue the autophagic activity was declined [74], underlining the potential impact of autophagy and lipid mediators in age associated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As EP2 signaling contributes to senescence in fibroblasts [72], and EP2 deletion reduces oxidative damage and severity of Alzheimer's disease [73], which suggests EP2 signaling as a potential link between defective autophagy and senescence/aging. Recently, it was shown, that in aged dermal fibroblasts and brain tissue the autophagic activity was declined [74], underlining the potential impact of autophagy and lipid mediators in age associated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…8). Furthermore, it was reported that mTORC1 activity is enhanced in aged tissue and linked to mitochondrial dysfunction independent of growth factor signaling [177], [178]. ALP-related proteins, demonstrating reduced MA in aging are summarized in Table 1.…”
Section: Proteostasis In Agingmentioning
confidence: 99%
“…Many of these alterations may arise, at least in part, from deterioration of basal autophagy and/or impairment of correct autophagy flux induction during cellular stress [2], although data assessing the role of autophagy in brain physiological aging is only beginning to emerge. In the human aged brain, a downregulation of autophagy genes including ATG-5, ATG-7, and BECN-1 has been observed [30], and brains of aged rodents exhibit increased MTORC1 activity together with a decline of ATG protein levels [31,32], suggesting decreased autophagic function. Similarly, mice carrying neural lineage-specific deletions of ATG-5 [27] and ATG-7 [28] show spontaneous and accelerated neurodegeneration.…”
Section: Autophagy In the Central Nervous System (Cns)mentioning
confidence: 99%